Focused Analysis of Exome Sequencing Data for Rare Germline Mutations in Familial and Sporadic Lung Cancer. Issue 1 (January 2016) - Liu, Yanhong; Kheradmand, Farrah; Davis, Caleb F.; Scheurer, Michael E.; Wheeler, David; Tsavachidis, Spiridon; Armstrong, Georgina; Simpson, Claire; Mandal, Diptasri; Kupert, Elena; Anderson, Marshall; You, Ming; et al.
ABSTRACT : Introduction : The association between smoking‐induced chronic obstructive pulmonary disease (COPD) and lung cancer (LC) is well documented. Recent genome‐wide association studies (GWAS) have identified 28 susceptibility loci for LC, 10 for COPD, 32 for smoking behavior, and 63 for pulmonary function, totaling 107 nonoverlapping loci. Given that common variants have been found to be associated with LC in genome‐wide association studies, exome sequencing of these high‐priority regions has great potential to identify novel rare causal variants. Methods : To search for disease‐causing rare germline mutations, we used a variation of the extreme phenotype approach to select 48 patients with sporadic LC who reported histories of heavy smoking—37 of whom also exhibited carefully documented severe COPD (in whom smoking is considered the overwhelming determinant)—and 54 unique familial LC cases from families with at least three first‐degree relatives with LC (who are likely enriched for genomic effects). Results : By focusing on exome profiles of the 107 target loci, we identified two key rare mutations. A heterozygous p.Arg696Cys variant in the coiled‐coil domain containing 147 ( CCDC147 ) gene at 10q25.1 was identified in one sporadic and two familial cases. The minor allele frequency (MAF) of this variant in the 1000 Genomes database is 0.0026. The p.Val26Met variant in the dopamine β‐hydroxylase ( DBH ) gene at 9q34.2 was identified in two sporadic cases; the minor allele frequency of this mutation is 0.0034 according to the 1000 Genomes database. We also observed three suggestive rare mutations on 15q25.1: iron‐responsive element binding protein neuronal 2 ( IREB2 ); cholinergic receptor, nicotinic, alpha 5 (neuronal) ( CHRNA5 ); and cholinergic receptor, nicotinic, beta 4 ( CHRNB4 ). Conclusions : Our results demonstrated highly disruptive risk‐conferring CCDC147 and DBH mutations.